Menggali Manfaat Sosial dan Manfaat Ekonomi dari Tradisi Rewang - Ari Widiyawati (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
The rewang tradition is a tradition of helping neighbors, friends, or family who have an event or celebration. This research aims to explore the sosial benefits and economic benefits of the rewang tradition in the Yosomulyo village community. Analyzed for this research using Peter M. Blau’s sosial exchange theory and this research used descriptive qualitative method. The result of the research show that rewang tradition provides many benefits to event owner rather than the cost of providing food and rewards for the para rewang. The sosial benefits of the rewang tradition are to establish of sosial relationships, increasing sosial solidarity, as a sosial capital, and acts of mutual assistance. The economic benefits of the rewang tradition are support for borrowing tools, reducing costs in organizing event, potential investment in merchandise, and investment in energy.